Good Governance, Sistem Pengendalian Intern, Konflik Kerja dan Kinerja Pemerintah dengan Motivasi Kerja sebagai Pemoderasi - Yuda, Gede Ananda Krista; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2022)
The purpose of this research is to examine the effect of Good Governance, internal control system (SPI), work conflict and government performance with work motivation as a moderating variable. The study was conducted at the OPD (Regional Apparatus Organization) in Klungkung Regency with a sample of 150 people. Data was collected by distributing questionnaires and the analysis technique in this study was Moderated Regression Analysis (MRA). The results showed that Good Governance had a negative effect, while SPI had a positive effect on government performance. Work conflict has no effect on performance. Work motivation is able to strengthen the influence of Good Governance on performance. Work motivation has not been able to strengthen the influence of the internal control system and work conflict on government performance. So work motivation has not moderated the effect of internal control system variables and work conflict on government performance. Keywords : Good Governance ; Internal Control Systems; Work Conflicts; Motivation; Performance.